Molecular Docking and ADME Studies of Natural Compounds of Agarwood Oil for Topical Anti-Inflammatory Activity - K. Yadav, Dharmendra; Mudgal, Vipin; Agrawal, Jyoti; K. Maurya, Anil; U. Bawankule, Dnyaneshwar; S. Chanotiya, Chandan; Khan, Feroz; T. Thul, Sanjog (Current Computer - Aided Drug Design, 2013)
Aquilaria agallocha Roxb. family, Thymelaeaceae, is an evergreen plant of South-East Asia, commonly described as aloe wood or agarwood. Traditionally, the bark, root and heartwood are used for their medicinal properties as a folk medicine for hundreds of years. Chemical analyses revealed that the bulk of the oil is constituted by agarospirol (12.5%), jinkoh-eremol (11.8%) and hinesol (8.9%) as major contributor. In the present work, a QSAR model for antiinflammatory activity of 10-epi-γ-Eudesmol, jinkoh-eremol, agarospirol and other compounds has been developed by multiple linear regression method. The r2 and rCV2 of a model were 0.89 and 0.81 respectively. In silico molecular docking study suggests that compound 10-epi-γ-Eudesmol, jinkoh-eremol and agarospirol are preferentially more active than other identified compounds with strong binding affinity to major anti-inflammatory and immunomodulatory receptors. The oil displayed a significant and dose dependent reduction of 12-O-tetradecanoylphorobol-13 acetate (TPA)- induced ear edema and MDA activity when compared with vehicle treated mice. Pro-inflammatory cytokines (IL-1β, IL-6 and TNF-α) were also reduced significantly in a dose dependent manner in all the TPA treated groups as compared to control. The present study indicates that agarwood oil significantly reduced the skin thickness, ear weight, oxidative stress and pro-inflammatory cytokines production in TPA-induced mouse ear inflammation model and contributed towards validation of its traditional use to treat inflammation related ailments.
Keywords: GC/MS analysis